The Costs of Urban Sprawl - Physical Activity Links to Healthcare Costs and Productivity - Trubka, Roman; Newman, Peter; Bilsborough, D. (Royal Australian Institute of Architects, 2010)
This is one of three companion papers taken from a study that assesses the comparative costs of urban redevelopment with the costs of greenfield development. The first paper, GEN 83: The Costs of Urban Sprawl – Infrastructure and Transportation, shows that substantial costs would be saved in infrastructure and transport if urban redevelopment were the focus. The second paper GEN 84: The Costs of Urban Sprawl – Predicting Transport Greenhouse Gases from Urban Form Parameters discusses the costs that can be linked to the transport carbon emissions that arise from suburban living.This paper discusses the health and productivity benefits of active-travel associated with the different urban forms due to levels of density, connectivity, and variety in amenity. It shows healthcare savings related to active forms of travel over a 50-year urban lifetime are quite small at $2.3 million for 1000 dwellings. But if these more walkable developments are pursued then the benefits to employment productivity are large, estimated to have a present value of $34 million. This is a substantial benefit that is comparable in scale to the savings in transport and infrastructure, as well as the social costs of greenhouse gases, and should provide a critical input to urban planning decision-making.